Avaliação da motilidade e do trânsito gastrintestinal de equinos após injeção epidural de morfina ou tramadol - Bertonha, Cândice Mara [UNESP] (2014)
Opioids provide analgesia, but have restricted use in horses because may lead to ileus and axcitement. Epidural opioids minimize side effects. Eight healthy horses (336.3 ± 33.4 kg) were used in three experimental groups to evaluate clinical, behavioral and gastrointestinal transit after epidural morphine (0.2 mg/kg) or tramadol (mg/kg) or NaCl 0.9%. Heart rate, respiratory rate, rectal temperature, intestinal motility, head height and time to first production of feces were evaluated. Intestinal transit was evaluated with the Lipe® method. The data were analyzed by a one-way analysis of variance or Friedman or Kruskal-Wallis and Student-Newman Keuls or Dunn’s tests as a post hoc. A value of p≤0.05 was considered significant. Tramadol or morphine produced did not change change in heart rate, respiratory rate, rectal temperature, head height and time to first production of feces. Epidural morphine decreased the gastrointestinal sounds score of four quadrants at 30, 60 and 120 minutes. Epidural morphine or tramadol did not change the intestinal transit. Opioid epidural did not cause ileus or colic. It is concluded that morphine reduced intestinal motility without changing the intestinal transit while the tramadol did not change intestinal motility or gastrointestinal transit